Social Protection Programs and the Future of the Poor and Vulnerable in Nigeria: Notes and Reflections from Lessons of History - Osewe, Akubor Emmanuel (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Existing studies argue that Social Protection Programs are designed to reduce poverty and vulnerability by promoting efficient labor markets. Therefore, the government must respect and promote the principles of non-discrimination, gender equality, responsiveness to social needs, social inclusion (including in the informal sector/economy), and respect for people's rights and dignity. This research uses qualitative field methods in the area and its surroundings. This research also uses historical documents from national archives and documentary data from newspaper reports, diaries, letters, and oral reports. The most common types of social protection include labor market interventions, social insurance, and social assistance. While this is the standard worldwide, especially in the ideal Social Contract between society and government, this has yet to be the case in most countries in the Developing World, especially Nigeria, in the last decade. So the impact is increasing poverty, neglect of older people, unemployment, disappointment, and tension, which leads to violent conflict. Therefore, this research attempts to build relationships between Nigeria's government and the Poor and Vulnerable Communities. The Nigerian government must show great commitment to the issue of social protection programs that are in line with global practices.